A REVIEW: NATURAL AND ARTIFICIAL RADIONUCLIDES AND RADIATION HAZARD PARAMETERS IN THE SOIL OF MOUNTAIN REGIONS IN SERBIA - Mitrović, Branislava M; Todorović, Dragana; Todorović, Dragana; Ajtić, Jelena; Ajtić, Jelena; Vranješ, Borjana; Vranješ, Borjana (Journal of Agricultural Sciences (Belgrade), 2020)
This paper presents a content of natural (40K, 238U, 226Ra and 232Th) and artificial (137Cs) radionuclides in the soil of the mountains Maljen, Tara and Kopaonik in Serbia. Soil samples were collected from different altitudes over 2002-2015. The specific activities of the investigated radionuclides were determined by gamma ray spectrometry. Further, based on content of natural radionuclides in the soil samples, we calculated radiation hazard parameters, i.e., radium equivalent, absorbed dose rate, annual effective dose equivalent, external hazard index, annual gonadal dose equivalent and excess lifetime cancer risk and compared them to previously published results from different parts of the Republic of Serbia.
Keywords: mountain ecosystem; gammaspectrometry; soils; radionuclides; Radiation; Doses